¿Qué es la productividad legislativa? Conceptos y factores que la explican - Huertas-Hernández, Sergio (Pontificia Universidad Católica del Perú, 2025)
The purpose of this article is to systematize and critically analyze academic literature on the dynamics of entry and approval of bills in legislative bodies. So far, research has identified several variables that influence legislative productivity, including institutional, political-electoral, attitudinal factors and those intrinsic to the characteristics of the legislation itself. In this sense, we propose a theoretical review that seeks to answer the question: what are the factors that explain legislative productivity? To this end, legislative productivity is defined as the relationship between the number of bills presented and those that manage to be approved within the legislative process. From this analysis, it is argued that literature has privileged the study of institutional and political-electoral factors, relegating the exploration of endogenous variables to the law, which represents a gap in the research agenda. Consequently, this paper highlights the need to broaden the theoretical and methodological approach in legislative studies through greater consideration of endogenous variables, which could offer new perspectives on the determinants of legislative production.

Este artículo tiene como objetivo sistematizar y analizar críticamente la literatura académica sobre la dinámica del ingreso y aprobación de proyectos de ley en los cuerpos legislativos. Hasta el momento, las investigaciones han identificado diversas variables que inciden en la productividad legislativa, incluyendo factores institucionales, político-electorales, actitudinales y aquellos intrínsecos a las características de la propia legislación. En este sentido, se plantea una revisión teórica que busca responder a la pregunta: ¿cuáles son los factores que explican la productividad legislativa? Para ello, la productividad legislativa se define como la relación entre el número de proyectos de ley presentados y aquellos que logran ser aprobados dentro del proceso legislativo. A partir de este análisis, se argumenta que la literatura ha privilegiado el estudio de factores institucionales y político-electorales, relegando la exploración de variables endógenas a la ley, lo que representa una brecha en la agenda de investigación. En consecuencia, este trabajo destaca la necesidad de ampliar el enfoque teórico y metodológico en los estudios legislativos mediante una mayor consideración de las variables endógenas, las cuales podrían ofrecer nuevas perspectivas sobre los determinantes de la producción legislativa.
What is legislative productivity? Concepts and factors that explain it
Keywords: Legislative productivity; Endogenous factors to the law; Legislative studies; Approval of bills; Productividad legislativa; Factores endógenos a la ley; Estudios legislativos; Aprobación de proyectos de ley; https://purl.org/pe-repo/ocde/ford#5.06.00